2007
DOI: 10.1186/2046-0481-60-3-161
|View full text |Cite
|
Sign up to set email alerts
|

A review of the renal system and diurnal variations of renal activity in livestock

Abstract: Kidneys are the main organs regulating water-electrolyte homeostasis in the body. They are responsible for maintaining the total volume of water and its distribution in particular water spaces, for electrolyte composition of systemic fluids and also for maintaining acid-base balance. These functions are performed by the plasma filtration process in renal glomeruli and the processes of active absorption and secretion in renal tubules, all adjusted to an 'activity-rest' rhythm. These diurnal changes are influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
(66 reference statements)
2
12
0
Order By: Relevance
“…Na þ and K þ concentrations were within reported reference ranges (Radostits et al 1974). Significant diurnal variations (P 5 0.05) in the plasma levels of Na þ and K þ have been observed in the present study and these are in agreement with the findings of Skotnicka et al (2007). Significant rhythmic fluctuation in blood Na þ and K þ concentrations with opposing patterns were found in our study; similar findings were reported by Yashiki et al (1995) and Table 2.…”
Section: Blood Ionized Electrolytessupporting
confidence: 95%
“…Na þ and K þ concentrations were within reported reference ranges (Radostits et al 1974). Significant diurnal variations (P 5 0.05) in the plasma levels of Na þ and K þ have been observed in the present study and these are in agreement with the findings of Skotnicka et al (2007). Significant rhythmic fluctuation in blood Na þ and K þ concentrations with opposing patterns were found in our study; similar findings were reported by Yashiki et al (1995) and Table 2.…”
Section: Blood Ionized Electrolytessupporting
confidence: 95%
“…Only a few studies have reported glomerular filtration rate (GFR) estimates in cows to date (Skotnicka et al 2007), because the traditional method of urinary clearance measurement requires an intravenous infusion and accurately and repeatedly timed blood and urine collections over a period of several hours. Moreover, the standard tracer inulin has an inherent disadvantage for cows because of extremely low solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on chronobiological aspects of physiological functions have been carried out mainly on humans and laboratory animals. A few studies have been carried out on livestock (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…They are responsible for maintaining the total volume of water and its distribution in particular water spaces, for electrolyte composition of bodily fluids and especially extracellular fluid, and for maintaining acid-base balance. Moreover, kidneys are responsible for expelling metabolites from the organism, especially for protein metabolism and other unnecessary and harmful substances, and at the same time maintaining the necessary substances in blood (4). Kidneys take part in the synthesis of hormones or their precursors such as renin, renal erythropoietic factor, calcitriol, and prostaglandins (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%